Habitat associations of six‐lined racerunners in longleaf pine managed with a short fire rotation for northern bobwhites - Isaiah W. Samek; Steven J. Price; Theron M. Terhune II; Darin J. McNeil (Ecosphere)
Abstract The longleaf pine (Pinus palustris) savanna ecosystem is an imperiled, fire‐dominated community that supports exceptionally high levels of species richness and endemism. Area of this community has declined by more than 95% due to unsustainable logging, fire suppression, and changes in land‐use practices. In recent decades, efforts to restore fire‐dominated communities like longleaf pine savanna have gained popularity, especially in light of benefits to charismatic species like the northern bobwhite (Colinus virginianus). Although reptiles are important members of this ecological community, far less information exists as to how this group responds to longleaf pine management, especially when game bird conservation is a primary management focus. Although bobwhite management in these systems is mostly synonymous with longleaf pine restoration, additional conservation practices aimed at game birds (promoting fallow fields, supplemental feeding, meso‐carnivore control, cross sectional mowing, etc.) might affect the extent to which squamates benefit from habitat management. To better understand how squamate reptiles may benefit from longleaf pine savanna managed for northern bobwhites, we surveyed for six‐lined racerunners (Aspidoscelis sexlineata) across a large, contiguous tract of longleaf pine with varied land cover characteristics, managed to maximize the conservation of northern bobwhites. Racerunner detection probability on transect surveys was low (p̂ = 0.23); however, occupancy probability was relatively high (ᴪ̂ = 0.60) across the property and driven by percent open ground (positive; 25‐m scale), percent grass cover (negative; 25‐m scale), and percent wetland (negative; 100‐m scale). Our findings support those of past studies about six‐lined racerunners in longleaf pine savannas suggesting the species thrives in the context of a short fire rotation (e.g., 2–3 years), even when game bird management is a primary objective of conservation efforts. Racerunners may also specialize on microhabitats (e.g., upland areas with relatively high bare ground cover) that occur most frequently in recently burned portions of bobwhite management units.